Internal Control, HR Competence, and PNBP Financial Reporting Reliability in South Bangka Agencies - Lusi Anggraini; Erita Rosalina; Wenni Anggita (Studi Akuntansi dan Bisnis Indonesia, 2026)
Purpose: The purpose of this study is to examine how internal control and Human Resource (HR) competency affect the accuracy of Non-Tax State Revenue (PNBP) financial reporting at the Ministry of Religious Affairs Office of South Bangka Regency and the Land Office (ATR/BPN). Methodology: This quantitative survey involved 56 participants. Data were analyzed using validity, reliability, classical assumption tests, multiple linear regression, t-test, F-test, and coefficient of determination, based on stewardship theory. Results: Internal control positively and significantly affects PNBP financial reporting reliability, whereas HR competence has no significant partial effect. Simultaneously, both variables significantly influenced reporting reliability, with an Adjusted R² of 0.780. Conclusions: Internal control is the dominant factor in improving PNBP financial reporting reliability, while both variables jointly explain 78% of the variation in central government vertical agencies in South Bangka Regency. Limitations: Only two central government vertical agencies in South Bangka Regency participated in this survey, which had a small sample size (56 respondents). Contribution: This study contributes to the development of public sector accounting research in the context of PNBP management, while also providing practical input for government agencies and policymakers to strengthen internal control and HR competence to produce reliable and accountable PNBP financial reporting.